Between home and the street. The political mobilisation of Catholic women during the Sexenio - Mínguez Blasco, Raúl (Hispania Nova, 2020)
The Sexenio Democrático (1868-1874) was a troubled period of the modern history of Spain in which the stable position achieved by the Catholic Church after the Concordat of 1851 was widely questioned. Due to the feminisation of Catholicism during the previous decades, the public debate about religion had an important gendered component. Despite the criticisms of revolutionaries and secularists, some women who presented themselves as Catholic wives and mothers publicly opposed the Government measures against the Church’s interests. This paper reflects on the capacity of agency of Catholic women and analyses how anti-liberalism conceived the link between the public and the private realm.
Keywords: Sexenio Democrático; gender; religion; secularism; anti-liberalism; agency